Prescribed performance spacecraft attitude tracking with disturbance observer: A performance-adjustable policy. Issue 8 (15th October 2022) - Niu, Zhaoxiang; Dai, Ming-Zhe; Gao, Junyang; Zhang, Chengxi; Wu, Jin
Abstract: In this paper, a prescribed performance control (PPC) scheme for spacecraft attitude tracking with anti-disturbance and performance-adjustable properties is proposed. The proposed controller is based on the barrier Lyapunov function (BLF) approach, which can arbitrarily adjust the state convergence performance and possess high steady-state performance. Compared with previous works, this strategy is more robust to external disturbances and thus has higher steady-state performance with low computing resource occupancy. What's more, it has the property of freely adjusting performance to meet the control objectives and performance requirements in different scenarios. Simulation results in this paper verify the effectiveness and superiority of the proposed method.